Jorge Insunza Becker. Escritos políticos e ideológicos, 1980-2015, T.3 - Insunza Gregorio de las Heras, Jorge (Ariadna Ediciones, 2022)
Jorge Insunza Becker (April 21, 1936-March 17, 2019) was one of the main leaders of the Chilean Communist Party since the 1960s. He joined the Communist Youth in 1954. In 1962 he was promoted to the Central Committee of the PC and from 1965 he was part of his Political Commission, the one that led the triumph of Salvador Allende in 1970. After the 1973 coup d'état, he was part of the first clandestine communist leadership that assumed the resistance to the dictatorship, together with Víctor Díaz, Américo Zorrilla, Mario Zamorano and Uldarico Donaire. With the return to democracy, he was one of the main figures who addressed the crisis in the socialist countries and the reconstruction of a project of the revolutionary left. Likewise, he had an active role in the agreements that allowed the return of the PC to Congress in 2010 and promoted the pact that allowed the communists to return to government with President Michelle Bachelet in 2014. The 4 volumes that we present cover a large part of the extensive journalistic and political work of this outstanding leader of the Chilean left. Arranged in chronological sequence, the texts collect the main part of his intellectual elaboration from the 1960s to the beginning of the 21st century (Volumes I, II, III). Volume IV is a selection of the most relevant of his career, facilitating the documentary relationship contained in the previous volumes. Undoubtedly, due to the breadth of the compilation made, the whole of this work will be extremely useful both for specialists in history, and for the consultation of interested parties in general. Finally, the contributions of Isabel Torres and Rolando Álvarez, both historians, help to enhance the meaning of the performance that Jorge Insunza took on.